Occurrence of uranium, thorium and rare earth elements in the environment: A review - Patel, Khageshwar Singh; Sharma, Saroj; Maity, Jyoti Prakash; Martín-Ramos, Pablo; Fiket, Željka; Bhattacharya, Prosun; Zhu, Yanbei (Frontiers in Environmental Science, 2023)
Uranium, thorium, and rare earth elements (REEs) are important strategic elements in today's world with a range of applications in high and green technology and power generation. The expected increase in demand for U, Th, and REEs in the coming decades also raises a number of questions about their supply risks and potential environmental impacts. This review provides an overview of the current literature on the distribution of these elements in different environmental compartments. For example, the processes of extraction, use, and disposal of U-, Th-, and REE-containing materials have been reported to result in elevated concentrations of these elements in air, in some places even exceeding permissible limits. In natural waters, the above processes resulted in concentrations as high as 69.2 mg·L-1, 2.5 μg·L-1, and 24.8 mg·L-1 for U, Th, and REE, respectively, while in soils and sediments they sometimes reach 542 mg·kg-1, 75 mg·kg-1, and 56.5 g·kg-1, respectively. While plants generally only take up small amounts of U, Th and REE, some are known to be hyperaccumulators, containing up to 3.5 g·kg-1 and 13.0 g·kg-1 of U and REE, respectively. It appears that further research is needed to fully comprehend the fate and toxicological effects of U, Th, and REEs. Moreover, more emphasis should be placed on developing alternative methods and technologies for recovery of these elements from industrial and mining wastes.